Dynamic Occupancy, Temporal Activity and Distribution Pattern of The Sulawesi Palm Civet (Macrogalidia musschenbroekii) in Bogani Nani Wartabone National Park - Patandung, Alfons; Saroyo; Singkoh, Marina Flora Oktavine; Rahman, Arief; Rahmanita, Dini (JURNAL BIOS LOGOS, 2025)
The Sulawesi Palm Civet (Macrogalidia musschenbroekii) is the only endemic carnivore on Sulawesi and a key mesopredator within Wallacean forest ecosystems. Despite its conservation significance, empirical information on its population dynamics and habitat associations remains limited. This study analyzes four consecutive years of camera‑trap monitoring (2021–2024) in Bogani Nani Wartabone National Park to evaluate occupancy patterns, environmental drivers, and temporal activity. Using a Bayesian dynamic occupancy framework, we estimated annual occupancy (ψ), detection probability (p), colonization (γ), and local extinction (ε), while examining the influence of elevation, slope, and additional landscape covariates. A consistent sampling effort of 49–50 cameras per year yielded 3,446–4,047 trap nights annually, with low but stable detection rates. Occupancy declined markedly from 0.86 in 2021 to 0.51 in 2024. Elevation and slope emerged as the strongest predictors of occupancy, indicating a preference for mid‑elevation forest habitats. Colonization (0.364–0.654) and extinction probabilities (0.286–0.587) exhibited high interannual variability, suggesting a metapopulation‑like dynamic influenced by habitat fragmentation and environmental instability. Temporal activity analysis revealed predominantly nocturnal and crepuscular behavior, consistent across years. These findings provide the most comprehensive ecological assessment of sulawesi palm civet to date and highlight the species’ sensitivity to habitat degradation. Long‑term monitoring, protection of montane forest corridors, and community‑based conservation programs are recommended to ensure long‑term persistence.